Travels and archaeology in South Chile - Bird, Junius Bouton, 1907-1982 (Book collections on Project MUSE., 1988)
"This is a remarkable book by one of the true geniuses in the field of anthropology during this century and one who provided valuable data for specialists in other disciplines as well."â€"H. M. Wormington"An engaging manuscript that should charm a broad audience."â€"Thomas F. Lynch"The field notes of Junius, and Peggy's diary, are valuable records of the excavations, artifacts, and interpretations of the best archaeologists to work in the southern tip of South America."â€"James G. GriffinJunius Bird's three great archaeological field achievementsâ€"at the Strait of Magellan in Chilean Patagoni.